Viral Hepatitis B/C Co-Infection and Its Association With Haematological and Virological Parameters in HIV Patients in Northern Ghana - Uzzah Mohammed Forgor; George Doopaar Billak; Nsoh Godwin Anabire; Gideon Kofi Helegbe (Anemia, 2025)
Human immunodeficiency virus (HIV) and viral hepatitis B (HBV) and C (HCV) share common routes of transmission and increase the morbidity and mortality of infected patients. In developing countries, including Ghana, HBV/HCV diagnoses are not routinely performed for patients in HIV clinics. Thus, the haematological impacts of hepatitis B/C are not evaluated before the inception of antiretroviral therapy (ART). This was a hospital-based cross-sectional study that assessed the prevalence of HBV and HCV infections among 135 HIV-1 infected patients in an HIV clinic in the Tamale Metropolis of Ghana using rapid diagnostic test kits. Haematological parameters and HIV load were evaluated and compared between HIV monoinfected and HIV-HBV or HIV-HCV coinfected patients. HIV-HBV and HIV-HCV coinfection rates were 8.9% and 5.9%, respectively. One participant (0.7%) was triply infected with HIV-HBV-HCV. HIV viral load was comparable in the different disease groups (p>0.5 for all comparisons). Neutrophils and lymphocyte counts were lower in HIV/HCV coinfected patients in contrast to HIV-monoinfected patients (p>0.05 for all comparisons). Significantly lower total WBC counts in HIV/HCV coinfected patients (p=0.002) as compared to HIV monoinfected patients were observed. Generally, the rates of haematological abnormalities (anaemia, leucopenia, lymphocytopenia, neutropenia and monocytopenia) were higher in coinfected cases than in monoinfected cases. In conclusion, patients at HIV clinics in the Tamale Metropolis of Ghana have a high rate of HBV/HCV coinfection, which can have a significant negative influence on haematological counts, particularly lymphocyte counts. This highlights the necessity of routine testing for HBV/HCV among HIV clinic patients to influence the choice of ART drugs prescribed.